I’m still quite young: women’s lived experience of precocious or premature menopause: a qualitative study among Egyptian women - Yasmine M. Osman; Hend Reda Ali El-Kest; Majed Awad Alanazi; Mostafa Shaban (BMC Nursing)
Abstract Background Precocious menopause, the cessation of ovarian function before age 40, presents complex physical, emotional, and socio-cultural challenges. In settings where fertility is central to a woman’s identity, early menopause can lead to stigma, psychological distress, and limited healthcare engagement. Nurses play a pivotal role in supporting affected women through education and empathetic care. Aim This study explored the lived experiences of Egyptian women diagnosed with precocious menopause, with a focus on physical and emotional challenges, cultural and familial dynamics, coping mechanisms, and interactions with healthcare providers—particularly nurses. Methods A qualitative descriptive design was employed. Fifteen women diagnosed with precocious menopause were recruited through purposive sampling from reproductive health clinics in Tanta city and surrounding areas in the Nile Delta region. Data were collected through semi-structured, in-depth interviews and analyzed using thematic content analysis. Results Participants reported significant disruption to self-identity and emotional well-being, compounded by cultural stigma and family pressures. Coping strategies included spiritual beliefs, peer support, and self-advocacy. Experiences with healthcare providers were mixed; nurses emerged as key figures in providing psychosocial support and education. Conclusion Findings underscore the need for culturally sensitive, nurse-led interventions to address the unique needs of women with precocious menopause. Enhancing nursing education and integrating psychosocial care into reproductive health services can improve health outcomes and quality of life. Clinical trial number Not applicable.